Social Security (Al-Takaful Al-Ijtima’i) in Islamic Perspective - May Dedu (International Journal of Nusantara Islam, 2020)
Law No.40 of 2004 is a legal umbrella for the implementation of social security in Indonesia. The basis for managing social security including health insurance is social compulsory insurance and equity. The social insurance system, requires social security financing based on contributions where each resident shares the burden of health expenditure that has been delegated responsibility to the Social Security Organizing Agency. This study will examine, how the views of health social security based on Law No.40 of 2004 concerning the National Social Security System and how the views of Islamic law on social security in Law No.40 of 2004. The results of this study indicate that: social in Islam, as a system that provides good for the community and rules in togetherness with the legal basis of the Koran or from others.